2016
DOI: 10.1016/j.bbacli.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between level of HbA1C and breast cancer

Abstract: BackgroundDiabetes and cancer are public health issues worldwide; studies have shown that diabetes is related to increased breast cancer mortality. The purpose of this study was to examine associations between HbA1C and obesity with tumor stage and mortality among breast cancer patients.MethodsData for 82 patients with breast cancer (36–89 years of age, diagnosed /treated 1999–2009) were provided by the University of Arkansas for Medical Sciences (UAMS) Data Trust Warehouse. Survival time was estimated from st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…This finding aligns with our observation that with each unit increase in HbA1c there was 1.6 times greater odds of cancer death (95% CI: 1.14 - 2.23). Additional studies have also reported that the increased mortality associated with poorly managed diabetes has been particularly appreciated in specific malignancies, such as colorectal cancer and breast cancer [ 53 , 54 ]. The exact relationship between diabetes and cancer mortality remains to be fully understood, but uncontrolled diabetes may have a direct effect on tumorigenesis, and indirect effects, such as influence of diabetes in medical decision making [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with our observation that with each unit increase in HbA1c there was 1.6 times greater odds of cancer death (95% CI: 1.14 - 2.23). Additional studies have also reported that the increased mortality associated with poorly managed diabetes has been particularly appreciated in specific malignancies, such as colorectal cancer and breast cancer [ 53 , 54 ]. The exact relationship between diabetes and cancer mortality remains to be fully understood, but uncontrolled diabetes may have a direct effect on tumorigenesis, and indirect effects, such as influence of diabetes in medical decision making [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with multiple other studies. 8,39,40 Among patients with solid cancers, prediabetic patients were found to be older in age and had a higher BMI compared to non-diabetic patients. 41 It is well-known that obesity affects survival and mortality of breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Obesity is associated with advanced clinicopathologic presentation of breast cancer and higher rates of disease recurrence and reduced overall survival. 39,44,45 The impact of obesity on risk for breast cancer has been shown to be affected by menopausal status in which obese postmenopausal women showed consistent increase of breast cancer risk compared to premenopausal patients. 46,47 The relationship between premenopausal obesity and breast cancer risk remains inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity, owing to its complex multifactorial disease nature is not only challenging the molecular scientists to decode its molecular basis but also the clinicians who are involved in treating, preventing and disease management. Approximately 30% of the world population is either overweight or obese [1]. So far, the specific molecular and cellular mechanisms through which environmental factors increase the risk of developing obesity in genetically susceptible individuals still remains to be a mystery.…”
Section: Introductionmentioning
confidence: 99%